2018
DOI: 10.1021/acssynbio.8b00194
|View full text |Cite
|
Sign up to set email alerts
|

Rational Control of Calcium Carbonate Precipitation by Engineered Escherichia coli

Abstract: Ureolytic bacteria (e.g., Sporosarcina pasteurii) can produce calcium carbonate (CaCO 3 ). Tailoring the size and shape of biogenic CaCO 3 may increase the range of useful applications for these crystals. However, wild type Sporosarcina pasteurii is difficult to genetically engineer, limiting control of the organism and its crystal precipitates. Therefore, we designed, constructed, and compared different urease operons and expression levels for CaCO 3 production in engineered Escherichia coli strains. We quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Details of the construction of the engineered E. coli strains and pre-culture growth conditions are described in Liang et al . 24 . In summary, for the E. coli HB101/ure-integration strain, a single copy of the urease gene cluster from S. pasteurii was inserted into the genome using a CRISPR-based technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the construction of the engineered E. coli strains and pre-culture growth conditions are described in Liang et al . 24 . In summary, for the E. coli HB101/ure-integration strain, a single copy of the urease gene cluster from S. pasteurii was inserted into the genome using a CRISPR-based technique.…”
Section: Methodsmentioning
confidence: 99%
“…While S. pasteurii and other native ureolytic microorganisms are difficult to engineer, the genome of E. coli is well-understood and can be readily genetically modified to express urease with different activities. We previously demonstrated that engineered ureolytic E. coli produces CaCO 3, and constructed several strains with a range of urease activities and corresponding precipitation kinetics 24 . Our engineered strain E. coli HB101/ure-integration, with relatively low urease activity and slow precipitation kinetics, produced larger calcite crystals than other E. coli strains with greater urease activity, such as E. coli HB101/pBU11.…”
Section: Introductionmentioning
confidence: 99%
“…PCC 7002 (referred to as Synechococcus in the following discussion) growing and inducing MICP as a result of the CO 2 -concentrating mechanism (CCM) (Jansson and Northen, 2010). The other two pathways took advantage of urea degradation, which is known to create a local alkaline environment and induce more MICP (e.g., ureolytic Sporosarcina pasteurii, Stocks-Fischer et al, 1999); in this study a bioengineered Escherichia coli strain (referred to as E. coli in the following discussion) that expresses urease operon from S. pasteurii (HB101:pBU11) (Liang et al, 2018;Bachmeier et al, 2002) and the Synechococcus sp. PCC 7002, which is also capable of ureolytic activity (Sakamoto et al, 1998), were grown with additional urea to induce MICP.…”
Section: Accessmentioning
confidence: 99%
“…PCC 7002, which is also capable of ureolytic activity (Sakamoto et al, 1998), were grown with additional urea to induce MICP. This initial study investigates the engineered ureolytic strain E. coli HB101:pBU11, which has the advantage to allow multiple genetic designs capable of greater rational control of CaCO 3 precipitation (Liang et al, 2018), leading to variable crystal morphology and nanomechanical properties (Heveran et al, 2019), opening exciting new possibilities for tailoring LBM properties. The three pathways are summarized in Figure 1.…”
Section: Accessmentioning
confidence: 99%
“…To demonstrate this ability in our system, we sought to produce capsules capable of biomineralization. To achieve this, we used a commercially available E. coli strain, HB101, transformed with the plasmid pBR322-Ure, which contains the urease gene cluster from the soil bacterium S. pasteurii (49). Urease catalyzes hydrolysis of urea, which leads to the formation of carbonate ions and an (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Programmable Biomineralization Of Capsulesmentioning
confidence: 99%